ENGLISH FOR FREELANCE ARCHITECTS ON FIVERR:AN ANALYSIS OF LINGUISTIC FEATURES AND RHETORICAL MOVES - Nadrotin Mawaddah; M. Hilmy Hidayatullah; Muhammad Fadlil Adhim (JR-ELT (Journal of Research in English Language Teaching), 2026)
Freelancing in Fiverr.com offers opportunities for fresh graduate architects to approach international clients, but it requires adequate English communication skills. The existing studies in this field offer unexplored spaces, especially in English for freelance architects in the global marketplace. Therefore, this study aims to explore how English is used to promote their services in architectural design on Fiverr and to communicate with clients via the chatbox. A genre analysis was applied to investigate the linguistic features and rhetorical moves of 12 freelance architects’ profiles, gig descriptions, and transactional chats. The results revealed that freelance architects’ profiles should represent architecture-related ESP linguistic features, including well-organized, business-style English with confident, polite, and promotional tones. In the freelancer-client chats, the priority was not in grammatically accurate and formal business-style sentences, but in comprehensibility, negotiation, customization, and, most crucially, optimal attention to the details of the clients’ requirements. In conclusion, English for freelance architects exhibits unique rhetorical and linguistic features and expands the communicative functions of English beyond conventional architectural ESP practices. Theoretically, this study contributes to ESP studies by extending toward a more digital, interdisciplinary, and market-oriented framework.